Fuzzy logic enhanced control for a single‐stage grid‐tied photovoltaic system with shunt active filtering capability. (4th July 2021) - Ayachi Amor, Yacine; Hamoudi, Farid; Kheldoun, Aissa; Didier, Gaëtan; Rabiai, Zakaria
Summary: In this paper, a three‐phase single‐stage grid‐connected photovoltaic (PV) system with active power filtering capability by means of a three‐level T‐type inverter is presented. The system is intended to fulfill many functions: harmonic mitigation, unity power factor operation, maximum power extraction from PV source, and so on. For the proposed system to achieve these tasks with a good dynamic performance, a new control strategy based on the fuzzy logic controller is developed. Fuzzy control has three main stages and each one requires many settings or selection of parameters. A new approach of setting the scaling factors which considerably affect the system's response is proposed. Furthermore, a methodology to properly set the fuzzy rules is suggested. The electrical power chain of the system comprises a farm of a PV source, three‐level T‐type inverter space vector pulse width modulation controlled, inductor filter, non‐linear load, and the utility grid. To evaluate the performance of the proposed control, a processor‐in‐the‐loop is performed as a hardware verification of the inverter control algorithm using a low‐cost STM32F4 discovery board, while the power circuit plant is modeled in the host computer using Matlab/Simulink. The obtained results are very satisfactory and confirm the role of each component, especially in terms of maximum power tracking, power quality, unity power factor operation, and control robustness. Abstract : A three‐phase single‐stage grid‐connected photovoltaic (PV) system with active power filtering capability by means of a three‐level T‐type inverter is presented in this work. The system is intended to fulfill many functions simultaneously: harmonic mitigation, unity power factor operation, maximum power extraction from PV source, and so on. A processor‐in‐the‐loop was performed to evaluate the performance of the system as a hardware verification of the inverter control algorithm using a low‐cost STM32F4 discovery board, while the power circuit plant is modeled in the host computer using Matlab/Simulink.